2020
DOI: 10.3390/foods9050677
|View full text |Cite
|
Sign up to set email alerts
|

Yield and Quality Characteristics of Brassica Microgreens as Affected by the NH4:NO3 Molar Ratio and Strength of the Nutrient Solution

Abstract: Microgreens are gaining more and more interest, but little information is available on the effects of the chemical composition of the nutrient solution on the microgreen yield. In this study, three Brassica genotypes (B. oleracea var. italica, B. oleracea var. botrytis, and Brassica rapa L. subsp. sylvestris L. Janch. var. esculenta Hort) were fertigated with three modified strength Hoagland nutrient solutions (1/2, 1/4, and 1/8 strength) or with three modified half-strength Hoagland nutrient solutions with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 36 publications
3
20
0
2
Order By: Relevance
“…It is currently unknown whether microgreen bioactive compounds have the same bioaccessibility as their mature counterparts, which has implications for bioavailability and bioactivity of compounds in vivo. Additionally, previous research has demonstrated that modulation of microgreens’ growing conditions (e.g., LED lighting and nutrient solutions) can enhance the concentrations of various health-promoting compounds such as β-carotene (provitamin A), anthocyanins, and α-tocopherol (vitamin E) ( 54 56 ). The impact that these enhancements have on bioaccessibility, bioavailability, and thus bioactivity of compounds should be evaluated, as should the impacts on consumer acceptability and sensory perceptions of microgreens.…”
Section: Discussionmentioning
confidence: 99%
“…It is currently unknown whether microgreen bioactive compounds have the same bioaccessibility as their mature counterparts, which has implications for bioavailability and bioactivity of compounds in vivo. Additionally, previous research has demonstrated that modulation of microgreens’ growing conditions (e.g., LED lighting and nutrient solutions) can enhance the concentrations of various health-promoting compounds such as β-carotene (provitamin A), anthocyanins, and α-tocopherol (vitamin E) ( 54 56 ). The impact that these enhancements have on bioaccessibility, bioavailability, and thus bioactivity of compounds should be evaluated, as should the impacts on consumer acceptability and sensory perceptions of microgreens.…”
Section: Discussionmentioning
confidence: 99%
“…Few works have so far addressed microgreens response to nutrient solution concentration, such as Murphy and Phill [24], Wieth et al [25] and Palmitessa et al [26]. Our study intended to shed the light on novel species from the Brassicaceae botanical family and assess the changes precipitated in microgreens performance, including the levels of yield and bioactive components, in the absence of nutrients supplemented through irrigation.…”
Section: Introductionmentioning
confidence: 99%
“…The protein content (N × 6.25) was determined by Kjeldahl nitrogen, according to the Association of Official Agricultural Chemists (AOAC) method 976.05 [26], and results were expressed as g 100 g −1 fresh weight (FW). The dietary fiber content was determined by the enzymatic-gravimetric procedure, according to the AOAC method [26] with some modifications reported by Palmitessa et al [27]. Samples (250 mg) were incubated in 32.5 mL of H 2 SO 4 0.64 N for 10 min at 100 • C, adding a few drops of n-octanol as an antifoam agent.…”
Section: Determination Of Protein and Dietary Fibermentioning
confidence: 99%
“…α-Tocopherol and β-carotene were extracted using the procedure described by Palmitessa et al [27]. Quantification of the two lipophilic compounds was carried out with high-performance liquid chromatography (HPLC) by using an Agilent Technologies HPLC system, model 1100 (Agilent Technologies, Palo Alto, CA, USA) equipped with a quaternary pump solvent delivery, thermostatic column compartment and diode array detector (DAD) (Agilent Technologies, Palo Alto, CA, USA).…”
Section: Determination Of α-Tocopherol and β-Carotenementioning
confidence: 99%